2016
DOI: 10.2214/ajr.15.15945
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Fractional b Value for Calculating Apparent Diffusion Coefficient in DWI

Abstract: The ADC value fluctuated when the b values used for calculation were higher than the fractional b value. Therefore, it is important to determine the fractional b value of the target tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…It was also observed that sampling low b-values increased parameter error as it pushed the slope to be artificially steeper due to perfusion effects. It was previously suggested that all non-zero b-values be greater than the fractional b-value (17). Sampling more high b-values appeared to slightly increase TPEsIVIM in contrast with a previous study (28).…”
Section: Associations With Clinicopathologic Factorscontrasting
confidence: 77%
See 1 more Smart Citation
“…It was also observed that sampling low b-values increased parameter error as it pushed the slope to be artificially steeper due to perfusion effects. It was previously suggested that all non-zero b-values be greater than the fractional b-value (17). Sampling more high b-values appeared to slightly increase TPEsIVIM in contrast with a previous study (28).…”
Section: Associations With Clinicopathologic Factorscontrasting
confidence: 77%
“…Portions of the cohort crucial parameter affecting ADC calculation (6,(13)(14)(15)(16). Furthermore, finding the b-value at which the contribution of perfusion-effects to the diffusional signal is negligible (the so-called fractional b-value) is critical in obtaining a perfusion-insensitive ADC (17,18). Due to the multistep estimation process of estimating IVIM parameters, the choice of b-value threshold in the initial estimation of the pure diffusion coefficient (D) and perfusion fraction (f) affects the final fitting (19,20).…”
Section: In Vivomentioning
confidence: 99%
“…This was possible because they both relate to cell density. However, mean ADC was slightly lower than mean D app , probably because mean D app was calculated according to multiple b values (30). MEM is a Gaussian diffusion model, but DKI is a non-Gaussian diffusion model.…”
Section: Discussionmentioning
confidence: 99%
“…The b-value corresponds to diffusion effects. The ADC is calculated on the basis of the difference in the signal intensity on DW images obtained at two different b values, corresponding to an exponential decrease in signal intensities [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%